Benefits Of Financing Institutions In The Production Of Cabbage Farming In Air Duku Village, Selupu Rejang Sub-District, Rejang Lebong District - Indah Fitria; Djatmiko Djatmiko (University of Prof. Dr. Hazairin, SH, 2022)
Agricultural development in indonesia is a country that has s majority of the population’s livelihood as a farmer.Rejang Lebong Regency area is the producer of vegetables. Ruralfinance institutional sometimes isn’t growing either as a result of too much government intervention. Based on the background of this research aims to know the role of financing improvement to farming vegetables the District Selupu Rejang Regency Rejang Lebong.